Coupling effect of active and reactive power controls on synchronous stability of VSGs - Deng, Han (2019)
The virtual synchronous generator (VSG) is emerging as a promising candidate for replacing synchronous generators in more-electronics power systems. Its fundamental objective lies in the regulation of active and reactive power for voltage forming and frequency control. To achieve tight power regulation, VSGs usually have closed-loop active power and reactive power controls. However, this paper reveals that the coupling effect between the active power control and the reactive power control will greatly change the synchronous stability of a VSG. Specifically, the maximum transferred active power and its associated power angle are reduced because of the coupling effect. To quantify this effect, a small-signal model of a grid-tied VSG is constructed, based on which the critical operation point is further analyzed. The power angle curve of VSGs with fixed reactive power output is compared with that of VSGs with constant output voltage amplitude. Finally, the effect of reactive power droop control in increasing the stable operation region is investigated in this paper.